2008
DOI: 10.3758/pbr.15.5.1022
|View full text |Cite
|
Sign up to set email alerts
|

Decision criteria do not shift: Commentary on Mueller and Weidemann (2008)

Abstract: The effects of base rates and payoffs on the shapes of rating receiver operating characteristic curves are inconsistent with the basic assumptions of signal detection theory (SDT), in particular the notion of a shifting decision criterion. Mueller and Weidemann (2008) Weidemann and Mueller's (2008) reply to this Comment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…We have shown that decision noise does indeed seem to have a large influence on confidence rating and forced choice responses (Mueller & Weidemann, 2008) and have argued that the RT results presented by Balakrishnan and MacDonald (2008) are consistent with a high degree of noise in the mapping between internal states and RT for a twoalternative forced choice response.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We have shown that decision noise does indeed seem to have a large influence on confidence rating and forced choice responses (Mueller & Weidemann, 2008) and have argued that the RT results presented by Balakrishnan and MacDonald (2008) are consistent with a high degree of noise in the mapping between internal states and RT for a twoalternative forced choice response.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, as Balakrishnan and MacDonald (2008) pointed out, these data seem at odds with a simple model that adjusts a decision criterion up or down on every trial depending on the previous classification response. We do not have an account for these results, but we note that more complex effects of the previous response on a decision criterion (possibly contingent on whether or not the previous response was correct) may be able to explain the small fluctuations in hit and false alarm rates that give rise to these results.…”
Section: Constraints In the Likelihood Ratio Functionmentioning
confidence: 79%
See 2 more Smart Citations
“…Confidence ratings turn out to be a convenient example of a strongly predictive measure, enough so that both the suboptimality and bias conditions are satisfied. However, they are satisfied in the situations predicted by sequential detection theory rather than by the static signal detection models (Balakrishnan & MacDonald, 2008).…”
Section: Sufficient Conditions For Suboptimal and Biased Decision Rulesmentioning
confidence: 95%